Model analisis penyampulan data rangkaian bersiri hierarki bagi pengukuran prestasi Universiti Awam di Malaysia - Rosmaini, Kashim (2021)
Measuring the performance of public universities is important to ensure efficient and effective utilization of allocated educational resources. Most of the previous studies on the application of Data Envelopment Analysis (APD) have focused more on measuring efficiency rather than effectiveness and ignored universities’ internal activities and the relation among the activities in a single model. As a result, the studies’ findings might be misleading. Besides, uncontrollable inputs and weight restrictions on shared input variables are not considered particularly in network APD (APDR). Thus, this study developed an alternative approach to measure a university’s performance by using the hierarchical serial APDR model by considering three performance dimensions, which are efficiency, effectiveness and overall performance. The uncontrollable inputs with weight restrictions on shared inputs are also included. There are three network models developed namely hierarchical APDR (APDRH) to measure efficiency, parallel APDR (APDRS) to measure effectiveness and hierarchical serial APDR (APDRSH) to measure the overall performance of the university. Since there are restrictions on weights that make the APDR models cannot preserve their linearity, an alternative approach is proposed to transform the non-linear APDR models into equivalent linear models. These three developed APDR models can analyze the performance of each university’s internal structure in details. The new hierarchical serial APDR (APDRSH) model has been tested to evaluate the three dimensions of performance of 14 schools in Universiti Utara Malaysia. Empirical findings showed that no schools were fully efficient and relatively effective since not all their internal functions were efficient. Furthermore, the application of this new performance measurement model can identify the university's internal activities which require more attention in an effort to improve the performance of the schools. This study has successfully produced a comprehensive performance measurement model of a university. The proposed conceptual model can become a basis for developing performance measurement models of other organizations.